Gamma Knife Radiosurgery Treatment for Metastatic Melanoma of the Trigeminal Nerve and Brainstem: A Case Report and a Review of the Literature - Halloran E. Peterson; Erik W. Larson; Robert K. Fairbanks; Wayne T. Lamoreaux; Alexander R. Mackay; Jason A. Call; John J. Demakas; Barton S. Cooke; Christopher M. Lee (Case Reports in Neurological Medicine)
Objective and Importance. Brainstem metastases (BSMs) are uncommon but serious complications of some cancers. They cause significant neurological deficit, and options for treatment are limited. Stereotactic radiosurgery (SRS) has been shown to be a safe and effective treatment for BSMs that prolongs survival and can preserve or in some cases improve neurological function. This case illustrates the use of repeated SRS, specifically Gamma Knife radiosurgery (GKRS) for management of a unique brainstem metastasis. Clinical Presentation. This patient presented 5 years after the removal of a lentigo maligna melanoma from her left cheek with left sided facial numbness and paresthesias with no reported facial weakness. Initial MRI revealed a mass on the left trigeminal nerve that appeared to be a trigeminal schwannoma. Intervention. After only limited response to the first GKRS treatment, a biopsy of the tumor revealed it to be metastatic melanoma, not schwannoma. Over the next two years, the patient would receive 3 more GKRS treatments. These procedures were effective in controlling growth in the treated areas, and the patient has maintained a good quality of life. Conclusion. GKRS has proven in this case to be effective in limiting the growth of this metastatic melanoma without acute adverse effects.